Punjab past and present : essays in honour of Dr. Ganda Singh - Harbans Singh, 1921-1998; Barrier, N. Gerald (Norman Gerald) (Punjabi University, 1976)
Articles on Sikhism and the history of Punjab; festschrift honoring the Sikh historian Ganda Singh, b. 1901.